Soft-gluon resummation for pseudoscalar Higgs boson production at hadron colliders - de Florian, D. (2008)
We compute the threshold-resummed cross section for pseudo-scalar MSSM Higgs boson production by gluon fusion at hadron colliders. The calculation is performed at next-to-next-to leading logarithmic accuracy. We present results for both the LHC and Tevatron Run II. We analyze the factorization and renormalization scale dependence of the results, finding that after performing the resummation the corresponding cross section can be computed with an accuracy better than 10%. © 2007 Elsevier B.V. All rights reserved.